2023
DOI: 10.1002/pol.20230516
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of well‐defined methacrylate copolymers and their use for stabilizing membrane proteins

Valentin Monjal,
Alexis Moreno,
David Glueck
et al.

Abstract: We describe the synthesis of a novel series of amphiphilic methacrylate copolymers composed of one hydrophobic monomer carrying a cyclohexyl group and one hydrophilic monomer carrying a short poly(ethylene glycol) chain comprising 6, 9, or 19 units. RAFT polymerization was used to yield well‐defined polymers. First, we studied the kinetic of this copolymerization and calculated the reactivity ratios according to different linear least‐squares (LLS) methods. We thus could demonstrate the statistical copolymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Studies have thus far shown that the inulins are as effective at extracting membrane proteins from E. coli membranes as DDM, based on the protein concentration in the soluble fraction [66] and allowed successful reconstitution of two oppositely charged cytochome P450s. [67] Other novel polymers include the anionic dendritic polyglycerol sulphate [68] and methacrylate copolymers [69] which have both shown potential for extracting stable and functional membrane protein.…”
Section: Polymersmentioning
confidence: 99%
“…Studies have thus far shown that the inulins are as effective at extracting membrane proteins from E. coli membranes as DDM, based on the protein concentration in the soluble fraction [66] and allowed successful reconstitution of two oppositely charged cytochome P450s. [67] Other novel polymers include the anionic dendritic polyglycerol sulphate [68] and methacrylate copolymers [69] which have both shown potential for extracting stable and functional membrane protein.…”
Section: Polymersmentioning
confidence: 99%